Formulation and Evaluation of Chitosan Beads of Levocetirizine Dihydrochloride - Vino S, Priyanka Paryani, Sajitha Lulu S, Ghosh AR (Journal of Applied Pharmaceutical Science)
Our study aims to design a controlled drug delivery system for Levocetirizine dihydrochloride by using chitosan beads. The beads were prepared by ionotropic gelation process, with Sodium tri poly phosphate (TPP) as an ionic agent. The formed beads were then further crosslinked using glutaraldehyde and the excess glutaraldehyde were then washed. The physical properties of the prepared beads such as beads sizes, shapes, encapsulation efficiencies, invitro release and degree of swelling were determined. The produced beads from all batches showed a very good spherical geometry with the bead size found to be less than 2mm. The drug loading efficiency was around 77.5% for all batches. The degree of swelling was found to be 1.4. FTIR, DSC and XRD studies shows the absence of the interaction between chitosan and the drug. This methodology of preparation of chitosan beads seems to be highly simple, commercially viable and a promising technique for controlling the release of drugs.
Keywords: Levocetirizine,swelling,chitosan,controlled-release,TPP